2007
DOI: 10.1128/iai.01604-06
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation of Human Gingival Epithelial Cells and Monocytes by Porphyromonas gingivalis Fimbriae

Abstract: Humans develop periodontitis in response to challenge by microbial dental plaque. Inflammation begins after perturbation of gingival epithelial cells by subgingival bacteria interacting through pattern-recognition receptors, including the Toll-like receptors (TLR). Porphyromonas gingivalis is a major periodontopathogen that interacts with epithelial cells through its cell surface fimbriae (FimA), leading to colonization and/or invasion. Previous work by our group has established membrane CD14 as an essential c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
67
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 29 publications
1
67
1
1
Order By: Relevance
“…The cells were seeded in 60-mm plastic tissue culture plates coated with type-I collagen, and incubated in 5% CO 2 and 95% air at 37°C. When the cells reached subconfluence, they were harvested and subcultured, as described (2).…”
Section: Cell Isolation and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…The cells were seeded in 60-mm plastic tissue culture plates coated with type-I collagen, and incubated in 5% CO 2 and 95% air at 37°C. When the cells reached subconfluence, they were harvested and subcultured, as described (2).…”
Section: Cell Isolation and Culturementioning
confidence: 99%
“…O ral mucosal epithelium, in addition to acting as a physiological barrier, plays a crucial role in initiating and augmenting oral defense mechanisms by releasing a variety of inflammatory molecules in response to oral microorganisms (1,2). Recognition of microorganisms is performed by pattern-recognition receptors that recognize highly conserved molecular patterns (microbial-associated molecular patterns) (3) such as LPS of Gram-negative bacteria.…”
mentioning
confidence: 99%
“…We have shown that the activation of TLRs by P. gingivalis induces the release of proinflammatory cytokines from gingival epithelial cells (9). Therefore, it might be expected that a reduction in cellular TLR4 is associated with a reduction in multiple "normal" host responses and, thus, increased susceptibility to chronic inflammatory diseases, including periodontal disease.…”
mentioning
confidence: 99%
“…Both cells were grown in DMEM with 10% fetal bovine serum (Atlanta Biologicals, Lawrenceville, GA), 100 U/ml of penicillin-streptomycin, 2 mM glutamine, and 100 nM nonessential amino acids. Primary human gingival epithelial cells (HGEC) were obtained from the University of Louisville School of Dentistry (Dr. D. Kinane) [37,38]. HGECs were grown in keratinocyte-serum-free medium (Invitrogen, Carlsbad, CA) containing 10 μg/ml of insulin, 5 μg/ml of transferrin, 10 μM of 2-mercaptoethanol, 10 μM of 2-aminoethanol, 10 mM of sodium selenite, 50 μg/ml of bovine pituitary extract, 100 U/ml of penicillin-streptomycin, and 50 ng/ml of fungizone.…”
Section: Cell Lines and Culturesmentioning
confidence: 99%